BUILDING A COLLABORATIVE RELATIONSHIP WITH AN INVOLUNTARY PARENT IN CHILD PROTECTIVE SERVICES - Kallas, Kristina; Toros, Karmen; Falch-Eriksen, Asgeir (Social Work/Maatskaplike Werk, 2022)
Building a collaborative relationship with an involuntary parent is challenging; however, the worker-client relationship is essential to promoting the wellbeing of the child and family. This article describes a small-scale qualitative study conducted with child protective workers in one region of Estonia. Findings indicate that in order to encourage involuntary parents to participate, it was crucial to learn what was provoking their resistance. Recognition was used to establish a collaborative relationship with involuntary parents. To reduce the unequal distribution of power, the parent was recognised as an equal partner and negative feelings were validated and understood as a normal reaction to intervention.